Improving corrosion and wear resistance of carbon steel piping system in oil and gas application through thermal spray coating techniques / Mitra Akhtari Zavareh - Mitra Akhtari, Zavareh (2015)
In petroleum and petrochemical industries, offshore and onshore systems have to function in an aggressive environment that exposes the production equipment components to thermal cycling, wear and corrosion. Although maintenance of material degradation in oil and gas is costly, internal and external parts of the equipment and pipelines must be well inspected and continually maintained. For this reason highly advanced corrosion and wear-monitoring systems must be installed in the critical areas of the plant to protect pipes and equipment from seawater and crude oil. Therefore, researchers are in search of advanced material and methods that could be applied in oil and gas pipelines and accessories for increasing their working time. The common manufacturing processing method for improving the surface of piping and accessories is overlay welding or cladding. This method has some limitations, such as its limitation for choosing materials. In addition, the high temperature of welding causes the final surface has some defects such as, thermal residual stress, cracking and distortion in the substrate. The method is also time-consuming and costly. However, the coating method provides a blend of unique properties with low cost. Thermal spray methods are cold spraying techniques that have a considerably less thermal stress, residual stress and other defects. Among different thermal spray coating techniques, high velocity oxygen fuel (HVOF) and plasma is the most commonly thermal spraying coating process to produce anti-wear and corrosion coatings with different types of materials such as metal, alloys, ceramic composite, etc. Furthermore, HVOF and plasma thermally sprayed coating process induces microstructure heterogeneities, which increase the corrosion and wear resistance. In this research, five different chemical compositions such as alloys and ceramic composite were chosen for increasing corrosion and wear resistivity of carbon steel piping. The chemical compositions are Inconel 625, NiCrCoAlY, Al8Si20BN, Cr3C2-25NiCr and Al2O3- 13%TiO2. For investigating properties of these chemical compositions, potentiodynamic polarization testing, open circuit polarization and electrochemical impedance spectroscopy (EIS) were used in 3.5% NaCl solution (seawater) at 30°C for 30 days. Corrosion was also measured by suspending the samples inside the crude oil at 60°C for 30 days. Measuring corrosion potential and corrosion current density from polarization curves and Tefal slope respectively established the general corrosion ranking of different materials. In addition, the correlation between individual microstructure features and their electrochemical response was established by EIS including equivalent circuit modeling. A wear property of each group of materials was investigated by pin-on-disk machine over a 9048.96 m sliding distance under different loads. The wear rate and weight loss results of each group materials had a different behavior. Some samples were more durable during applying different loads and the rate of weight loss in these samples was very limited. Comparing all the corrosion and wearing results illustrate that the ceramic composite samples have the highest to resistance corrosion and wear behavior. Significantly less effective than the ceramic composite samples, the alloy coated samples showed considerable anti-corrosion and wear behavior.